Water use efficiency of different production techniques for zucchini - Anita Cristina Costa da Silva; Willian Fernandes de Almeida; Luiz Antonio Lima; Mayra Carolina de Oliveira; Alexandre Lasmar Guimarães (Acta Scientiarum. Agronomy, 2019)
The effects of pulse drip, drip line position and soil mulch on water use efficiency in yields of zucchini cv. Clarinda were evaluated. The experiment was conducted in the experimental area of the Engineering Department of the Federal University of Lavras, Lavras, Minas Gerais State, Brazil, for two years. For the first year of the experiment, the experimental design was a randomized block design with a 2 x 2 x 2 factorial design (continuous and pulse drip irrigation, surface and subsurface dripping, with and without plastic mulch), with four replications. For the second year of the experiment, the design was completely randomized in a 2 x 2 x 2 factorial design with eight treatments and five replications. In relation to the position of the drip line, the subsurface drip line was installed at a 0.15-m depth, and the soil mulch was made with double-sided plastic (white/black). The results indicated that pulse drip irrigation did not affect the yield of zucchini and that soil mulch increased the yield and water use efficiency. In terms of the drip line position, the subsurface drip line increased the yield in the first year, but it had no effect on water use efficiency.